The marketing policy of the major Russian enterprise in the chemical industry - Khakimzianova Alsu Saetzianovna, Galanin Sergey Fedorovich, Galanina Sofia Sergeevna,; Salihovna, Hakimova Anora; German Yurievich, Fan-Yung (Opción, 2019)
The study aims to investigate sources of the marketing policy of the major Russian enterprise in the chemical industry via both quantitative and qualitative methods. As a result, newspaper advertising and the record-keeping documents allow us to characterize the methods of the marketing of their products by such major Russian industrialists as the Krestovnikov brothers. As a result of the study, it can be concluded that they recognized advertising as the most important instrument of sales policy.